Implementasi Kurikulum Berbasis Berkeadilan Gender di MA Mu’allimat NU Kudus - Safinatun Naja; Partono (Tapis: Jurnal Penelitian Ilmiah, 2026)
This study aims to explore the implementation of a gender-based curriculum at MA Mu’allimat NU Kudus. The research employs a descriptive qualitative approach. Primary data were collected through interviews, observations, and documentation, while secondary data were obtained from relevant literature. The main informant in this study was the deputy head of the curriculum division at MA Mu’allimat NU Kudus. Data validity was ensured through source, method, and theoretical triangulation. The data were analyzed using data reduction, data display, and conclusion drawing techniques.The findings indicate that the gender-based curriculum is implemented through three main components: the national curriculum, local content, and the hidden curriculum. Within the national curriculum, the madrasa adapts learning materials and instructional approaches to support the empowerment of female students. In the local content, classical Islamic texts are taught using a critical gender perspective. Meanwhile, the hidden curriculum is implemented through extracurricular activities, including female education programs that foster gender awareness and skills.Overall, the implementation of the gender-based curriculum contributes to reducing gender bias and strengthening the role of women in the public sphere. This study highlights the importance of integrating equality values into Islamic education and recommends the reinforcement of similar curriculum models in other educational institutions to promote more inclusive and gender-equitable social transformation.